The (Unfulfilled) Potential of Data Marketplaces - Pantelis Koutroumpis; Aija Leiponen; Llewellyn D. W. Thomas (The Research Institute of the Finnish Economy (ETLA), 2017)
Although industrial datasets are abundant and growing daily, they are not being shared or traded openly and transparently on a large scale. We investigate the nature of data trading with a conceptual market design approach and demonstrate the importance of provenance to overcome protection and quality concerns. We consider the requirements for data marketplaces, comparing existing data marketplaces against standard market design metrics and outline both centralized and decentralized multilateral designs. We assess the benefits and potential operational features of emerging multilateral designs. We conclude with future research directions.
Keywords: D47; D82; K12; L14; O34; 330; Data marketplaces; Data trading; Market design